2016
DOI: 10.1007/s00253-016-7835-7
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment using microalgae: how realistic a contribution might it be to significant urban wastewater treatment?

Abstract: Microalgae have been proposed as an option for wastewater treatment since the 1960's but still this technology has not been expanded to an industrial scale. In this paper, the major factors limiting the performance of these systems are analysed. The composition of the wastewater is highly relevant, and especially the presence of pollutants such as heavy metals and emerging compounds. Biological and engineering aspects are also critical and have to be improved to at least approximate the performance of conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
139
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(167 citation statements)
references
References 37 publications
0
139
1
4
Order By: Relevance
“…The filtration of microalgae also allows operating at shorter hydraulic retention times (HRTs) and longer biomass retention times (BRTs), enabling to recover large quantities of nutrients without washing out the microalgae culture (Gao et al, 2019). This can improve the microalgae performance while increasing the nutrient load to the system which would reduce the large areas of land that are needed for microalgae cultivation (Acién et al, 2016). By way of example, Bilad et al (2014) reported in lab conditions 9fold higher microalgae biomass productivity than a PBR system when HRT and BRT were decoupled by membrane filtration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The filtration of microalgae also allows operating at shorter hydraulic retention times (HRTs) and longer biomass retention times (BRTs), enabling to recover large quantities of nutrients without washing out the microalgae culture (Gao et al, 2019). This can improve the microalgae performance while increasing the nutrient load to the system which would reduce the large areas of land that are needed for microalgae cultivation (Acién et al, 2016). By way of example, Bilad et al (2014) reported in lab conditions 9fold higher microalgae biomass productivity than a PBR system when HRT and BRT were decoupled by membrane filtration.…”
mentioning
confidence: 99%
“…BRT: biomass retention time; PS: pumping system; NPV: non-photic volume; HRT: hydraulic retention time; a: HRT = 2-4 days; b: HRT = 4.5 days; group of numbers (1,2,3,4,5,6): non statistically significant differences.…”
mentioning
confidence: 99%
“…[10] in an SBR photo-bioreactor operated at SRT of 15 days and MLSS concentrations up to 2.41 g/L. MLSS concentrations in the range of 0.5 to 2.0 g/L are expected and depend on the photo-bioreactor type and the culture conditions [6]. Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, new concepts are emerging for other algal biomass uses such as animal feed or chemicals, bioplastics, and biofuels [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation